Cateter central de inserção periférica em neonatologia e pediatria: as vozes das enfermeiras - Oliveira, Cristine Ruviaro de (2012)
The Peripherally Inserted Central Catheter (PICC), or Peripherally Inserted Central Venous Catheter (PICVC), is an intravenous device inserted through a superficial vein of the extremity that progresses for the blood flow and for insertion procedures, until the third distal of the vena cava, stayed in central level. Currently, the nurse is the main responsible for assessing the need of the use of this device and is the most professional directly involved in the insertion, maintenance and prevention of complications. The aim of this study was: to understanding the role of nurses in the use of PICC in neonates and children in a teaching hospital. The specific aims were: to describe the role of nurses in the use of PICC in neonates and children in a teaching hospital; to analyze the risks and benefits of using PICC considering the patient safety in neonates and children in a teaching hospital and to discuss the limits and possibilities of the use of PICC in neonates and children in the context of a teaching hospital. It was a qualitative and exploratory-descriptive study realized of April to May 2012. The subjects were 20 nurses from the Pediatric Inpatient Unit, Neonatal Intensive Care Unit and Pediatric, Emergency Room Pediatric and Center of Bone Marrow Transplantation, of a teaching hospital in the southern Brazil. The Creative Sensitive Method, using three dynamics of sensitivity and creativity: Tree of Knowledge, Knowledge Body and Almanac. Data were sumitted to Discourse Analysis in this current French. The ethical aspects of the research were respected in accordance with Resolution 196/96 of the National Health Council, and the project was approved with the protocol number 00541812.6.0000.5346. The results indicate that the nurse holds a prominent position in the use of PICC in neonates and children, being that its preparation starts in the graduation, complemented with the legal training and extends into daily practice, racioning clinically and evaluating risks and benefits. The incorporation of new technologies in intravenous therapy brought the concern with the patient safety. The nurses have care to stabilize the child hemodynamically, manipulate your body the little possible and not to expose them to risk of infection, with observation of asseptic techniques. So, they choose carefully the acess and not exceed three attempts. In order to prevent the stress of the patient, family and group, should be pay attention in the guidance, analgesia and sedation. It is recommended to invidualization / uniqueness of each case with the implementation of the Systematization of Nursing Care (SNC), it enables the SNC, records and highlights the work of nurses. Thus, it is expected that this professional can assume and maintain autonomy in the face of indications, insertion, maintenance and removal of the PICC, working with technical and legal competence. Thus the nurse should be prepared for this activity developing it responsibly, conscious and preventive.